An Evidence-Based Approach to Technology for Identifying Interests and Improving Behavior in Young Children - Srivastava, Sandeep (Digital Repository of Theses, 2025)
Growth refers to the progressive increase in a child's physical attributes (weight, height, etc.), while development involves the progressive acquisition of various skills. Children begin learning from birth, and their learning journey represents a developmental process throughout life. Growth and development are continuous processes. Kids respond to receptive vernacular and develop expressive language as per their ambiance. Technology has a vast and frequent impact on the growth of children. Consequently, understanding technology's role in these small kids' lives will help them develop interest recognition and morphed behavior. This surge in use has led to much attention on the consequences of technology utilization and how it impacts kids’ brains and social, emotional, cognitive, and physical development. This research dissertation studies the use of technology in ascertaining the interests of infants and children, as well as improving their behavior. The research advances in the provision of behavioral analytical techniques and acceptances of new-borns and children in different categories and subcategories with the aid of technology. The system would involve machine learning and analysis of data in order to understand the interest of infants and children and allow parents and other caregivers to engage them in activities or interventions around the areas of interest which are beneficial for their growth. The research also looks into the correlations between various primary and secondary categories in an attempt to identify the possibilities of cross-training that enhance cognition and psychomotor development of infants and young children. Tied to the objectives of this study is the understanding of how children’s lives are influenced through the use of scientific innovations. The increase in technology has raised concern with regards to the impact it has on the brain development of children and on their emotions, social and cognitive aspects, as well as physical development. The technology use has to be easy and effective in interest identification. The results of this study may be useful for parents, guardians, and teachers, so they are able to make informed decisions regarding the introduction of technology to infants and preschool-aged children. By providing recommendations on the optimal use of technology, the project seeks to improve knowledge on infant health and parenting